The Role of the West Java Indonesian Broadcasting Commission (KPID) in Preventing Citizen Panic Related to News and Information Regarding Covid-19 - Yadi Supriadi; M. Subur Drajat; Nuril Lutfiah Saleh; Anisa Suci R.; Audi Siti Nur Huda (MediaTor (Jurnal Komunikasi), 2020)
The distribution of news and information about Covid-19 occurred amid a pandemic. It certainly creates a panic impact on some people, especially those who do not have adequate media literacy skills. This panic leads to uncontrolled behavior and unfiltered acceptance of information. This study seeks to investigate how the West Java Regional Indonesian Broadcasting Commission (KPID) Role in Preventing Citizen Panic Regarding News and Information Regarding Covid-19. Official broadcast media with high credibility have often ignored because people tend to prefer media with high accessibility, such as the internet and social media. From this condition, news and information about Covid-19 have often mixed with hoaxes readily accepted by some people. This research uses qualitative methods with case study research, with data collection techniques carried out through interviews, literature study, and observation. The results showed that in overcoming public panic, KPID West Java encourages broadcast media to always pay attention to the Broadcasting Code of Conduct and Broadcast Program Standards (P3SPS) and health protocols in every broadcasting activity. Also, media literacy has consistently remained calm and aware of various hoax information, such as Covid-19